Integral bridge abutment with composite dowels: structural scheme and failure patterns - Zhihua Xiong; Di Di; Hui Wang; Zhenhua Pan; Markus Feldmann (Fracture and Structural Integrity)
This paper presents a novel integral abutment design incorporating a composite dowel girder and H-shaped steel pile abutments to enhance load-bearing capacity and construction efficiency. Numerical analysis is conducted to investigate the failure modes, load-transfer mechanisms, and ultimate bearing capacity of the integrated abutment joint. A parametric study examines the influence of key factors, including steel girder web thickness and the reinforcement ratio of the deck and abutment, on structural performance. Results indicate that abutment failure is primarily attributed to concrete compression failure beneath the steel girder. Based on the findings, a formula for predicting the ultimate bearing capacity of the integrated abutment joint is proposed. Under the same steel girder depth and bottom plate width, the steel consumption of the integral abutment proposed in this work is reduced while the section has a slightly higher bearing capacity compared that of the traditional I-shaped steel girder.